2019
DOI: 10.1021/acsomega.8b03102
|View full text |Cite
|
Sign up to set email alerts
|

Polar Interactions Play an Important Role in the Energetics of the Main Phase Transition of Phosphatidylcholine Membranes

Abstract: Conformational changes of membrane proteins are accompanied by deformation in the surrounding lipid bilayer. To gain insight into the energetics of membrane deformation, the phase behavior of dimyristoylphosphatidylcholine (DMPC) membranes in the presence of the dipole potential, ψ d , modifiers was investigated by differential scanning calorimetry. 7-Ketocholesterol, which weakens ψ d and reduces membrane-perpendicular dipole–dipole repulsion, causes a discrete se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…21,55,56 Considering the nonideal mixing of FA-glu with PLs, the fluidity of the LBL comprising FA-glu and PLs then relied on the polar interactions of their head-groups that are accounted in terms of the changes in enthalpy (ΔH) and the nonpolar interactions for the hydrophobic chains accounted as changes in the entropy. 57 The T m that largely defines the entropy state for an LBL account for the relative motilities of the FA-glu and PLs combined, which is then governed by both the polar 58 and nonpolar interactions. Thus, the changes in H and T m for the PLs representing E. coli O157:H7 and L. monocytogenes, upon dissolution of FA-glu, provided an estimate of the alterations in the physical statethe LBL fluidityof the cell membranes of these bacterium types.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…21,55,56 Considering the nonideal mixing of FA-glu with PLs, the fluidity of the LBL comprising FA-glu and PLs then relied on the polar interactions of their head-groups that are accounted in terms of the changes in enthalpy (ΔH) and the nonpolar interactions for the hydrophobic chains accounted as changes in the entropy. 57 The T m that largely defines the entropy state for an LBL account for the relative motilities of the FA-glu and PLs combined, which is then governed by both the polar 58 and nonpolar interactions. Thus, the changes in H and T m for the PLs representing E. coli O157:H7 and L. monocytogenes, upon dissolution of FA-glu, provided an estimate of the alterations in the physical statethe LBL fluidityof the cell membranes of these bacterium types.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These transitions can be altered by compounds that disrupt the phospholipid bilayer packing structure. The classic example is cholesterol. , If ATP were interacting with the phospholipid bilayer and altering the strength of the interactions between individual phospholipids, a change in the main phase transition temperature and enthalpy would be expected.…”
Section: Resultsmentioning
confidence: 99%
“…The free energy, ΔG, was obtained from ΔG(z) = − RT ln p(z), where p(z) is the normalised number density of a given system component at position z along the bilayer normal, calculated from MD simulations of a proton near the surface of a hydrated DMPC lipid bilayer. Reprinted from Wolf et al (2014) with permission from Elsevier monovalent ions (Garcia-Manyes et al 2005;Garcia-Manyes et al 2006;Garcia et al 2019;Piantanida et al 2017). In addition, simulations have demonstrated changes to the area per lipid, order parameters, diffusion coefficients and orientations of the headgroup dipole (Böckmann et al 2003;Cordomí et al 2008;Gurtovenko and Vattulainen 2008;Reif et al 2017;Vácha et al 2009).…”
Section: Interactions Of Alkali Ions With Membranesmentioning
confidence: 99%
“…Both protons and alkali ions are small cations that have been shown to bind to the water-lipid interface of phospholipid membranes and, through these water-ion-lipid interactions, have the capacity to change the structure and physicochemical properties of membranes (Böckmann et al 2003;Cordomí et al 2009;Cranfield et al 2016;Deplazes et al 2017;Garcia-Manyes et al 2005;Garcia-Manyes et al 2006;Garcia et al 2019;Koynova and Caffrey 1998;Petelska and Figaszewski 2002;Piantanida et al 2017;Reif et al 2017;Vácha et al 2009). As we will outline in this review, in many cases, the reported findings on how protons and alkali ions interact with phospholipid membranes This article is part of a Special Issue dedicated to the '2018 Joint Conference of the Asian Biophysics Association and Australian Society for Biophysics' edited by Kuniaki Nagayama, Raymond Norton, Kyeong Kyu Kim, Hiroyuki Noji, Till Böcking, and Andrew Battle.…”
Section: Introductionmentioning
confidence: 99%